"الحوكمة وتحقيق أهداف التنمية المستدامة 2030 دراسة حالة الجزائر( 2015 – 2020) " - باوية, خيرالدين (جامعة الوادي university el-oued)
تطرقت الدراسة الى دور الحوكمة وتحقيق أهداف التنمية المستدامة 2030 والوقوف على حالة الجزائر في هذا خلال الفترة الممتدة ما بين 2015 – 2020 , من خلال ذلك تم تناول سياسات الحوكمة المحلية والدولية وفق خطة التنمية المستدامة 2030 وإنعكساتها على الجزائر, كما أنه خلال التطرق إلى مضامين سياسات الحوكمة المحلية والدولية وكيفية تأثيرها على المسار تحقيق أهداف التنمية المستدامة 2030, حيث تم إستنتاج أنه لتحقيق شروط التنمية المستدامة لا تتم إلا بإشراك ثلاثية القطاع العام, القطاع الخاص و المجتمع المدني كما خلصت الدراسة إلى أن مستقبل التنمية في الجزائر مرتبط مباشرة بآليات ومؤشرات الحوكمة لتحقيق متطلبات التنمية المستدامة نظرا لعدة إعتبارات من بينها محاربة الفساد وتفعيل عامل التشاركية, لذلك يجب العمل على الرفع درجة النمو الإقتصادي والمساواة بين الشعوب وضمان حقوق الأجيال القادمة.The study touched on the role of governance and achieving the goals of sustainable development 2030 and standing on the case of Algeria in this during the period between 2015 - 2020, through which the local and international governance policies were dealt with according to the 2030 sustainable development plan and their implications for Algeria, as well as by addressing the contents of the policies of Local and international governance and how it affects the path of achieving the goals of sustainable development 2030, as it was concluded that to achieve the conditions for sustainable development can only be achieved with the participation of the public sector, the private sector and civil society. The study also concluded that the future of development in Algeria is directly linked to the mechanisms and indicators of governance to achieve the requirements of Sustainable development due to several considerations, including fighting corruption and activating the participatory factor, so work must be done to raise the degree of economic growth and equality between peoples and guarantee the rights of future generations
م.س.ع.22
Keywords: الحوكمة - التنمية المستدامة - دراسة حالة الجزائر- سياسة عامة; Governance - sustainable development - Algeria case study - public policy